Requirements for an Integrated in situ Atlantic Ocean Observing System From Coordinated Observing System Simulation Experiments - Gasparin, Florent; Guinehut, Stephanie; Mao, Chongyuan; Mirouze, Isabelle; Rémy, Elisabeth; King, Robert R.; Hamon, Mathieu; Reid, Rebecca; Storto, Andrea; Le Traon, Pierre-Yves; Martin, Matthew J.; Masina, Simona (Frontiers in Marine Science, 2019)
A coordinated effort based on Observing System Simulation Experiments (OSSEs) has been carried out for the first time by four European ocean forecasting centers in order to provide insights on the present and future design of the in situ Atlantic Ocean observing system from a monitoring and forecasting perspective. This multi-system approach is based on assimilating synthetic data sets, obtained by sub-sampling in space and time an eddy-resolving unconstrained simulation, named the Nature Run. To assess the ability of a given Atlantic Ocean observing system to constrain the ocean model state, a set of assimilating experiments were performed using four global eddy-permitting systems. For each set of experiments, different designs of the in situ observing system have been assimilated, such as implementing a global drifter array equipped with a thermistor chain down to 150 m depth or extending a part of the global Argo array in the deep ocean. While results from the four systems show similarities and differences, the comparison of the experiments with the Nature Run generally demonstrates a positive impact of the different extra observation networks on the temperature and salinity fields. The spread of the multi-system simulations, combined with the sensitivity of each system to the evaluated observing networks, allowed us to discuss the robustness of the results and their dependence on the specific analysis system. By helping define and test future observing systems from an integrated observing system view, the present work is an initial step toward better-coordinated initiatives for supporting the evolution of the ocean observing system and its integration within ocean monitoring and forecasting systems.